The validity of Carhart model for shares in financial, banking and insurance businesses – A quantile regression approach - Phạm, Lệ Mỹ; Phan , Thị Thanh Thuý (Hue University Journal of Science: Natural Science, 2021)
Quantile regression is a very powerful tool for financial research and risk analysis when a market encounters shocks. In this paper, we use the quantile regression method to assess the parameters of the Carhart model for four factors: market return, equity size, value size, and momentum and test the validity of this model for shares in the financial, banking and insurance businesses when shocking news appears in the financial market. The results show that when the financial market is unstable, the firm capitalization (size), the book-to-market ratio, and the momentum affect the stock returns.